T THE RELATIONSHIP BETWEEN FAMILY SUPPORT WITH HEALING RATES PATIENT COVID 19 THOSE WORK ARE IN ISOLATION IINDEPENDENT - Yenny Richa Wahyu Ramayanti Yenny Richa Wahyu Ramayanti (PROFESSIONAL HEALTH JOURNAL, 2023)
Covid-19 is an infectious disease caused by a new type of corona virus, namely Sars-coV-2 and was first discovered in Wuhan, China on December 31, 2019. Covid-19 has caused various impacts on human life. These conditions cause the emergence of feelings of fear and anxiety in the community.This study analyzes the relationship between family support and the recovery rate of Covid 19 patients undergoing independent isolation. Method: The sampling technique used is purposive sampling. The technique for collecting data is through filling out questionnaires and open interviews about the support provided by families with healing rates of Covid 19 who are undergoing self-isolation. Health education about types of family support regarding Covid 19 prevention in the form of theory with the Lecture and Question and Answer method via offline. Result and analysis: Based on the Spearman Rank test, the value of sig = 0.03 and the value of = 0.05 means that P < then H0 is rejected, meaning that there is a relationship between family support and the recovery rate of Px Covid 19 who are undergoing independent isolation in the Rw 09 Village of Kesatrian Malang City. Almost half (42.5%) of Px Covid 19 who are undergoing independent isolation in the Rw 09 area, Kesatrian Village, Malang City, have good family support. Respondents always improve their immune quality by always thinking positively and asking for support from their family and social support.